2020
DOI: 10.1038/s41586-020-2452-0
|View full text |Cite|
|
Sign up to set email alerts
|

Structure of human GABAB receptor in an inactive state

Abstract: Human GABA B G protein-coupled receptor (GPCR), a member of the class C family, mediates inhibitory neurotransmission and is implicated in epilepsy, pain, and addiction 1 . A unique GPCR known to require heterodimerization for function 2 – 6 , its two subunits, GABA B1 and GABA B2 , are structurally homologous but perform distinct and complementary functions. GAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 58 publications
4
90
1
4
Order By: Relevance
“…Changes in the 7TM subunit interaction interface upon agonist activation of the GABA B -R have been quantified by cysteine cross-linking studies [26], and is also described in the in the newly released papers describing cryo-EM structures [6,7]. The 7TM domain interface interactions in the inactive state is formed by TM3 (GABA B1 )-TM5 (GABA B2 ) and TM5 (GABA B1 )-TM3 (GABA B2 ) interactions and that the interactions between the protomers are facilitated through ionic interactions stabilized by aromatic residues [6,9,26]. The distance between the backbones of TM5 in each monomer is 8 Å and thereby much shorter than the distance between the homodimers in the inactive mGlu5, which is 21 Å [6,44].…”
Section: Transmembrane Domainsmentioning
confidence: 99%
See 3 more Smart Citations
“…Changes in the 7TM subunit interaction interface upon agonist activation of the GABA B -R have been quantified by cysteine cross-linking studies [26], and is also described in the in the newly released papers describing cryo-EM structures [6,7]. The 7TM domain interface interactions in the inactive state is formed by TM3 (GABA B1 )-TM5 (GABA B2 ) and TM5 (GABA B1 )-TM3 (GABA B2 ) interactions and that the interactions between the protomers are facilitated through ionic interactions stabilized by aromatic residues [6,9,26]. The distance between the backbones of TM5 in each monomer is 8 Å and thereby much shorter than the distance between the homodimers in the inactive mGlu5, which is 21 Å [6,44].…”
Section: Transmembrane Domainsmentioning
confidence: 99%
“…Mao et al further suggest that G-proteins may bind to one of the subunits at a time due to sterically hindrance, favoring the GABA B2 as this was the most frequent populated distribution found in processing the cryo-EM data [ 6 ]. The recent cryo-EM structures describe that the extracellular half of the 7TM region of both monomers are occupied by a phospholipid, in both the active and inactive conformations, at a site corresponding to the orthosteric binding sites in most family A GPCRs [ 6 , 8 , 9 ]. Moreover, a “lid” is formed over the lipids in each subunit by residues located in the ECL2 of GABA B1b , and all ECLs in GABA B2 including the linker [ 8 , 9 ].…”
Section: Structure Of the Gaba B Receptormentioning
confidence: 99%
See 2 more Smart Citations
“…Two classes of cholesterol binding sites for β 2 AR were found by NMR spectroscopy [ 139 ], while MD simulation studies indicated direct interactions between cholesterol and GPCRs, including A 2A AR and β 2 AR [ 117 , 135 , 140 , 141 ]. Concerning GPCRs overall, at least seven distinct cholesterol binding sites have been observed in crystal structures of different receptors [ 136 , 137 , 142 , 143 , 144 , 145 , 146 , 147 ] ( Table 1 and Figure 3 ). MD simulations also revealed seven potential cholesterol binding sites on the surface of β 2 AR.…”
Section: Interactions Of Gpcrs With Their Membrane Environmentmentioning
confidence: 99%